Empowering PKK Mothers in Klagensrampat Village: Accelerating income through ASMAN TOGA management - Fajri, Mega Barokatul; Bait, Jennifer Farihatul; Pratiwi, Elasari Dwi (Community Empowerment, 2025)
The purpose of this community service is to empower PKK mothers in Klagensrampat Village, Maduran District, Lamongan Regency, through the "Income Acceleration Through ASMAN TOGA Management" program. This program aims to increase participants' knowledge regarding the classification and function of TOGA plants, as well as encourage product innovation using TOGA as raw materials. The stages of the activity include training and mentoring as well as monitoring and evaluation. This training is provided with materials on classifying types of toga and their properties, creating innovative products, packaging design materials and digital marketing. The results of this activity show an increase in participants' knowledge and skills, especially in creating new products that are innovative and have high selling value. This activity has succeeded in creating products that have the potential to be marketed internationally, including herbal medicine in the form of liquid drinks (temulawak and turmeric), herbal medicine powder (ginger and lemongrass), and gummy candy (temulawak and lime). In addition, participants also gain an understanding of how to design attractive packaging and logos, as well as effective digital marketing strategies. The target partners showed very active and enthusiastic participation during the mentoring process.